Acute Digital Ischemia Associated with Closed Injury - Janák, David; Ručka, David; Kudlička, Jaroslav; Rohn, Vilém; Lindner, Jaroslav; Kittnar, Otomar (Prague medical report, 2015)
Injury of an artery has a significantly worse prognosis for the patient than a venous injury. Blunt injuries of lower limb digital arteries with the development of acute ischemia present a very rare phenomenon. A crush mechanism with a defect of the non-wetted surface of vessel's inner part and the development of subsequent thromboischemic lesion is essential for the development of ischemia. We report a blunt injury of the right lower limb in a patient after incorrect stepping with subsequent lesion of digital arteries and the development of acute acral ischemia of the right toes.
Keywords: mužské pohlaví; Male; tupá poranění; Humans; Wounds, Nonpenetrating; Toes; lidé; Vascular System Injuries; angiografie; Trombolysis; prsty nohy; poranění nohy (od hlezna dolů); Ischemia; Foot Injuries; Angiography; ischemie; poranění cév; dospělí; Adult; Closed injury